PENERAPAN METODE PROBLEM SOLVING BERBASIS PEMBELAJARAN STEM DALAM MENGATASI LIMBAH DOMESTIK PADA SISWA KELAS V SDN SEKARPUTIH 1 - Berliana Nandya Zana; Eky Setiowati; Dika Ning Pratiwi; Bela Putri Widiyanti; Nadilatus Salsabila; Ulin Nuha (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to implement a problem-solving method based on STEM education to address domestic waste among fifth-grade students at UPTD SPF SDN Sekarputih 1, with the ultimate goal of reducing the increasing amount of domestic waste through economic activities. The problem-solving method was chosen as an educational approach to enhance students' understanding of the benefits of carrot plants, including how to grow and utilize them to reduce organic waste. The study employs an experimental design involving fifth-grade students at UPTD SPF SDN Sekarputih 1 as research subjects. Data were collected through observations, written tests, and interviews to evaluate the efficacy of this approach in improving students' understanding and competencies. The findings suggest that the implementation of the problem-solving method based on STEM education not only enhances students' understanding of carrot plants but also improves their comprehension of domestic waste and their ability to design sustainable solutions. The implications of this study suggest that this approach can be an effective alternative in environmental education at the elementary school level, strengthening STEM skills while teaching students to address environmental challenges.